2011
DOI: 10.1074/jbc.m111.278747
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Interface between the Pleckstrin Homology (PH) and Kinase Domains of Akt Protein Is Sufficient for Hydrophobic Motif Site Phosphorylation in the Absence of mTORC2

Abstract: The pro-survival kinase Akt requires phosphorylation at two conserved residues, the activation loop site (Thr-308) and the hydrophobic motif site (Ser-473), for maximal activation. Previous reports indicate that mTORC2 is necessary for phosphorylation of the hydrophobic motif and that this site is not phosphorylated in cells lacking components of the mTORC2 complex, such as Sin1. Here The Akt/protein kinase B Ser/Thr protein kinases play a central role in signaling downstream of phosphatidylinositol 3-kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…These results indicate that disrupting the PH-KD contacts leads to constitutive phosphorylation of AKT. In agreement with this result, a recent study showed that deletion of AKT1 PH domain led to its constitutive S473 phopshorylation (22). breast, 48 nonsmall-cell lung (NSCLC) adenocarcinoma (adeno), 43 NSCLC (squamous), 43 renal carcinoma, 37 melanoma, 33 gastric, 32 ovarian, 15 esophageal, 11 hepatocellular, 10 small-cell lung cancer, and 6 others (5 lung large cell and 1 lung cancer other) (Dataset S2).…”
Section: Resultssupporting
confidence: 76%
“…These results indicate that disrupting the PH-KD contacts leads to constitutive phosphorylation of AKT. In agreement with this result, a recent study showed that deletion of AKT1 PH domain led to its constitutive S473 phopshorylation (22). breast, 48 nonsmall-cell lung (NSCLC) adenocarcinoma (adeno), 43 NSCLC (squamous), 43 renal carcinoma, 37 melanoma, 33 gastric, 32 ovarian, 15 esophageal, 11 hepatocellular, 10 small-cell lung cancer, and 6 others (5 lung large cell and 1 lung cancer other) (Dataset S2).…”
Section: Resultssupporting
confidence: 76%
“…Moreover, when the myrAkt mutant was compared in experiments with phospho-mimicking non-myristoylated Akt mutants, their ability to rescue the phenotypic effects of Rictor knock-out was similar (48). Another potential explanation for mTORC2-independent activation of myr-Akt was provided by work of Warfel et al (39). The authors showed that Ser-473 of Akt mutants lacking pleckstrin homology domain, like our myr-Akt, can be still phosphorylated in the absence of functional mTORC2.…”
Section: Discussionmentioning
confidence: 99%
“…phosphorylates itself (39). Thus, although myr-Akt mutant is a good tool to provide evidence for sufficiency of Akt to rescue dendritic arbor simplification upon Rictor knockdown, more experiments are needed in the future with use of additional Akt mutants to fully describe the mechanism of Akt regulation by mTORC2 in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…DNA-PK and casein kinase II are predicted to phosphorylate OSR1 S339 (http://scansite.mit.edu). Akt, like the Ste20 kinase noted above, can autophosphorylate its own hydrophobic motif site; this mechanism is enhanced by mutation of the pleckstrin homology domain or prolonged inhibition of mTORC1 (30,49,52). Autophosphorylation is an intriguing possibility because OSR1 can exist as an activation loop-swapped dimer (53).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that one or more other kinases can also phosphorylate the PF1 site on OSR1 following prolonged mTOR inhibition. Enzymes other than mTORC2 phosphorylate the Akt hydrophobic motif under certain circumstances; these include Akt itself, the DNA-dependent protein kinase (DNA-PK), and the Tank binding kinase (30,(49)(50)(51). DNA-PK and casein kinase II are predicted to phosphorylate OSR1 S339 (http://scansite.mit.edu).…”
Section: Discussionmentioning
confidence: 99%